Consolation: What it is and what it is not - Roxberg, Åsa (Nordisk Tidsskrift for Helseforskning, 2024)
What is consolation [comfort], what is it not and is consolation relevant to professional care today. These questions are analysed in this essay. The starting point is Roxberg’s thesis about consolation. The ethical explication of ’personhood’ and of inner and outer truths are moulding the theoretical framework and the horizon of understanding is foremost from the Book of Job in the Old Testament. Job is afflicted by disease and accidents and his friends try to console him, but Job is not consoled. Their consolation is non-consolation, and the question is why? The friends lack openness to Job’s suffering and their locked perceptions about the right consolation for Job are understood as the hermeneutic idea of the conflict of interpretations is missing.  On the playfield of consolation there is only one team to play against, their own truth. Consolation becomes a lonely team player without any team to play against.
Keywords: Consolation; suffering; care; The book of Job; hermeneutics